PRINCIPLES OF JUSTICE FOR PERSONS WITH DISABILITIES IN THE JUDICIAL PROCESS - Salsabila, Alifia Azzahra; Cahyani, Shabrina Areta; Ardesta, Friscellia Rahel; Khoirunnisa, Aulia; Setiani, Adinda Ririn (Realism: Law Review, 2025)
The implementation of a system with fair principles for all groups, including persons with disabilities, requires full supervision due to their vulnerability to discrimination as victims, perpetrators, or witnesses. Law Number 8 of 2016 concerning Persons with Disabilities serves as the legal foundation for protecting and respecting the rights of persons with disabilities. However, challenges persist in its practical implementation. A case in Sumenep, as reflected in Decision Number 135/Pid.B/2024/PN.Smp, serves as the main focus of this study, emphasizing the application of justice principles for persons with disabilities who often face obstacles, particularly regarding adequate accommodation and accessibility, leading to injustice in the rights they receive .This research employs a normative juridical method with a case study approach and secondary data analysis to identify the principles of justice applied, assess the implementation of existing regulations, and examine the criminal justice system in Indonesia. The findings indicate that discrimination in protecting the rights of persons with disabilities persists due to weak regulations on the types of disabilities victims face and the accommodations provided. Based on this decision, it is imperative to provide training for law enforcement officers to be more assertive in implementing justice for all citizens of Indonesia, including persons with disabilities, as victims, witnesses, or perpetrators of criminal acts. Strengthening protection mechanisms is essential to ensuring tangible justice and creating an inclusive criminal justice system that safeguards their rights.